Cholangio-digestive anastomosis in biliary cancer: Presentation of 15 cases and review of the literature - Estefan, Alberto; Kamaid, Emil; Gomez Fossati, Carlos; Delgado, Bolivar; Praderi, Raúl (Cirugía del Uruguay, 1977)
The authors study mediate and delayed results obtained by C.D. A. in palia ti ve treatment of biliary cancer. They analyze 15 of their own cases and 240 others from 31 series. Anatomosurgical basis of C.D. A. are described, as well as those procedures which have proved clinically useful, with stress on two original technical variations: transversal intubation of hepatic ducts in left cholangioanastomosis and mediate cholangiogastrostomy. As simplest and most efficient procedure they propose left cholangiojejunostomy, approaching segment canal III via the round ligament. In connection with prognosis, tumoral infiltration of hepatic confluence is important and also has considerable bearing on therapy C.D. A . is proposed as the last therapeutic resource in tumoral blocking of transverse fissure of the liver; and as an alternative to hepatoanastomosis and external hepato or cholangiostomies. C.D. A. indication and election procedure should be sustained by careful evaluation of site, lesions and, fundamentally, hepatocholangiogram.